2017
DOI: 10.1002/ange.201708614
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐freezing, Conductive Self‐healing Organohydrogels with Stable Strain‐Sensitivity at Subzero Temperatures

Abstract: Conductive hydrogels are a class of stretchable conductive materials that are important for various applications. However, water‐based conductive hydrogels inevitably lose elasticity and conductivity at subzero temperatures, which severely limits their applications at low temperatures. Herein we report anti‐freezing conductive organohydrogels by using an H2O/ethylene glycol binary solvent as dispersion medium. Owing to the freezing tolerance of the binary solvent, our organohydrogels exhibit stable flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 30 publications
0
94
0
1
Order By: Relevance
“…[15][16][17][18][19] There are three prerequisites for the intrinsic healing process: (1) intimate contact between the fractured interfaces, (2) diffusion of the polymer chains across the fractured interfaces, and (3) reconstruction of the reversible covalent/noncovalent bonds to repair the fracture. Therefore, manual/ external interventions are always required to meet these three intrinsic healing prerequisites, such as elevating temperature, [7][8][9][20][21][22] irradiating light, [10][11][12]23,24 swelling/softening the material by solvents, 22,[25][26][27][28][29][30] applying pressure, [30][31][32] and others. Even so, intrinsic healing materials, capable of healing under ambient conditions are generally soft and deformable and mostly in the form of hydrogels or elastomers that feature high polymer chain mobility/flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] There are three prerequisites for the intrinsic healing process: (1) intimate contact between the fractured interfaces, (2) diffusion of the polymer chains across the fractured interfaces, and (3) reconstruction of the reversible covalent/noncovalent bonds to repair the fracture. Therefore, manual/ external interventions are always required to meet these three intrinsic healing prerequisites, such as elevating temperature, [7][8][9][20][21][22] irradiating light, [10][11][12]23,24 swelling/softening the material by solvents, 22,[25][26][27][28][29][30] applying pressure, [30][31][32] and others. Even so, intrinsic healing materials, capable of healing under ambient conditions are generally soft and deformable and mostly in the form of hydrogels or elastomers that feature high polymer chain mobility/flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength (Figure 3B), fracture strain ( Figure 3C), and Young's modulus (Figure 3D) of the organohydrogels were higher than that of original Eu-alginate/PVA hydrogel, which can be ascribed to the synergistic effect of the multiple hydrogen bonds and the dense polymer networks. For instance, the tensile strength of OHG SB increases from 0.58 ± 0.06 MPa to as high as 5.62 ± 0.41 MPa, fracture strain raised from 4.07 ± 0.04 to as high as 7.63 ± 0.02 and Young's modulus ascended from 0.16 ± 0.01 to 1.08 ± 0.03 MPa as the displacement time gradually increased to 6 h. The tensile strength is higher than many of the previously reported organohydrogels, such as polydopamine decorating carbon nanotubes (PDA-CNT)/copolymer of acrylamide (AM) and acrylic acid (AA) (PAM-co-PAA) organohydrogel (0.07 MPa stress, 7.01 strain, Han et al, 2017), PVA/poly(3,4ethylenedioxythiophene):polystryrene sulfonate (PEDOT:PSS) organohydrogel (2.1 MPa stress, 7.60 strain, Rong et al, 2017), and gelation organohydrogel (2.06 MPa stress, 6.88 strain, Qin et al, 2019), as shown in Figure S1. The dramatic enhancement in mechanical properties of the organohydrogels is directly related to crosslinking density, which dominated by the largely increased hydrogen bonds between the cryoprotectant molecules and polymer chains in the organohydrogels (Pan et al, 2018).…”
Section: Mechanical Properties Of the Eu-alginate/pva Organohydrogelsmentioning
confidence: 77%
“…However, almost all of the hydrogels swollen a large amount of water in polymer networks cannot resist a cold or hot environment (Wei et al, 2014(Wei et al, , 2015Wang W. et al, 2018), hindering the application of tough hydrogels in harsh conditions. Subzero temperature results in freezing of hydrogels, while high temperature lead to drying (Rong et al, 2017;Zhang et al, 2018). Freezing and drying cause the hydrogels to hard, opaque and dry, which undoubtedly change the integrated mechanical properties of hydrogels, leading to unstable nature under wide temperature range (Han et al, 2017;Lou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate these two synthesis strategies, we also utilized the EG as the organic solvent to synthesize PAAm organohydrogels [13], and the mechanical properties were determined ( Figure 6). As mentioned previously, the mechanical performance of the EG-based organohydrogels from each synthesis strategy might be also influenced by two opposite factors: the hydrogenbonding-induced strengthening and solvent effect for in-situ gelling or swelling for solvent- Since we knew the amount of each component in the organohydrogels, if we assumed that the polymer and glycerol in the matrix would remain and only water would lose during the heating and long-term storage, we could estimate the proportion of the dispersion medium in the remaining gels (Figure 4c,d).…”
Section: Mechanical Properties Of the Eg-based Paam Organohydrogelsmentioning
confidence: 99%